The Role of the Knowledge Management in International Strategy - LIN, JUNG-AN (2016)
Knowledge, which includes tacit and explicit, performs a leading role when a multinational corporation (MNC) is in the process of internationalisation as it can help the MNC to sustain its place in the market for a long time. However, MNC finds it difficult to manage the course of knowledge acquired from worldwide and share the knowledge within companies because they are operating in a global context. Although previous literature emphasises that knowledge management is critical for successful global operation, they did not focus much on the implementation of knowledge management in international strategies. Due to the above reason, this paper aims to understand the process of top management in applying knowledge management on their decision of international strategy and also investigate the factors that affect the decision-making. Semi-structured Interviews with six MNC representatives were administrated, and content analysis was adopted. Three main themes were established through the interview data, which were global strategic challenges arising in international strategies, influential factors of knowledge management on international strategies and process of knowledge management in developing an international strategy. By deeply understanding the three most important themes, this study concludes the enablers reinforce knowledge management through which to help the top management to develop the international strategy.